A New Approach on Exact Controllability of Semilinear Predator Prey Model - Shukla, Chandan; Shukla, Anurag; Kumar, Rajeev; Singh, Arun Kumar; Gautam, Arstu (Discontinuity, Nonlinearity, and Complexity, 2026)
Using the fundamentals of functional differential equations, we provide explicit controllability results for a family of semilinear nonautonomous predator-prey systems in this study. The suggested method is simple in terms of hefty estimations as compared to standard ways because it avoids the well-known fixed point theory approach. It's also effective because it doesn't require any of the unnatural conditions that fixed point theory requires. Finally, we looked at a case study with simulation findings.